The Influence Of The Flipped Classroom Model and Independent Learning on The Critical Thinking Capability Of Science and 5 Class Students in Primary School - Riska, Riska; Marjo, Happy Karlina; Purwantiningsih, Ary (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The low quality of education in Indonesia can be seen, among other things, at the basic education level. According to the TIMSS & PIRLS International Study Center survey, it shows that the quality of basic education in Indonesia, especially in the field of science, is only ranked 44th out of 47 countries that took part in the assessment with an average science score of 397. Aim: This research aims to determine the extent of the influence of the flipped classroom model and independent learning on scienceas critical thinking skills. Method: This research is a type of quantitative research that discusses The influence of the flipped classroom model and independent learning on the science and science critical thinking abilities of fifth grade elementary school students. The method used in this research is a quasi-experimental method which is a development of the pure experimental method of analysis of variance (ANOVA) with a 2x2 treatment by level design. The techniques for collecting data are questionnaires, tests and documents. The sampling technique uses a stratified random sampling procedure. Results and discussions: Based on the results of the research conducted, there was an interaction between the flipped classroom model and independent learning on critical thinking skills in Science and Technology. The results of the ANOVA test showed that the Fcount value = 19.28 and the Ftable value = 4.11 at the level  = 0.05. These results show that Fh > Ft so that there is an interaction between the use of the flipped classroom model and independent learning in influencing students' science and science critical thinking abilities. Conclusion: Based on the results of data analysis, hypothesis testing and research discussion results, it can be concluded that there is a positive and significant influence of the flipped classroom model and learning independence on the thinking ability of social science students in grade V of elementary school.